2014
DOI: 10.1002/joc.3989
|View full text |Cite
|
Sign up to set email alerts
|

Statistical downscaling of precipitation using a stochastic rainfall model conditioned on circulation patterns – an evaluation of assumptions

Abstract: For climate impact assessment regarding hydrology, the availability of long precipitation time series with high temporal and spatial resolution is essential. A possible approach to obtain this data is the statistical downscaling of precipitation simulated by a global climate model (GCM) using a stochastic rainfall model with parameters conditioned on circulation patterns (CP). This approach requires: (1) the existence of a strong relationship between CP and precipitation, (2) the sufficient reproduction of CPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Instationarities in the relationship between weather types and local variables are a long-debated issue in downscaling (IPCC, 2007), and several studies indicated their presence (e.g. Widmann and Schär, 1997;Beck et al, 2007;Haberlandt et al, 2015). Those classifications were, however, based on sea level pressure only Haberlandt et al, 2015) or additionally included geopotential height (Widmann and Schär, 1997).…”
Section: On the Optimal Classificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Instationarities in the relationship between weather types and local variables are a long-debated issue in downscaling (IPCC, 2007), and several studies indicated their presence (e.g. Widmann and Schär, 1997;Beck et al, 2007;Haberlandt et al, 2015). Those classifications were, however, based on sea level pressure only Haberlandt et al, 2015) or additionally included geopotential height (Widmann and Schär, 1997).…”
Section: On the Optimal Classificationmentioning
confidence: 99%
“…Widmann and Schär, 1997;Beck et al, 2007;Haberlandt et al, 2015). Those classifications were, however, based on sea level pressure only Haberlandt et al, 2015) or additionally included geopotential height (Widmann and Schär, 1997). The addition of temperature and specific humidity might provide a better classification also in terms of capturing transient changes in local climate by changes in weather pattern sequencing.…”
Section: On the Optimal Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…[Bardossy and Plate 1992;Esteban et al 2005;Stahl et al, 2006;Huth et al, 2008;Demuzere et al 2009;Lee and Sheridan 2011]. Recent studies [Bardossy and Pegram 2011;SaprizaAzuri et al, 2013;Haberlandt et al, 2014] have illustrated the usefulness of incorporating ACPs in downscaling and bias correction methodologies. In particular Sapriza- demonstrated that several aspects of the spatio-temporal non-stationarity of catchment scale spatially-distributed rainfall fields can be reproduced by decomposing the rainfall generating process into several, time-stationary, stochastic rainfall generating processes (SRGPs).…”
Section: Background and Motivationmentioning
confidence: 96%